THE 7 HABITS OF HIGHLY EFFECTIVE PEOPLE: POWERFUL LESSONS IN PERSONAL CHANGE - COVEY, STEPHEN R (London Simon & Schuster, 2013)
A timeless bestseller
Keywords: Success-Psychological aspects; Character; Self-actualization (Psychology); Personality